Fatigue-fracture-resistant self-adhesive ion skin stable in extreme environment and preparation method and application of fatigue-fracture-resistant self-adhesive ion skin
By combining the low crosslinked polydimethylsiloxane elastomer and perfluoroether rubber with the stretchable ionic conductive elastic fiber web through mechanical interlocking technology, a fatigue-resistant self-adhesive ionic skin is formed, which solves the problem of insufficient stability and mechanical properties of the stretchable ionic conductor in the prior art in extreme environments, and achieves the improvement of high mechanical properties and environmental stability.
Patent Information
- Application Number
- CN202411809740.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing tensile ion conductors are difficult to maintain stability in extreme environments, and their mechanical properties and fatigue fracture resistance are insufficient, which limits their use in applications such as soft robots.
Chemically inert low crosslinked polydimethylsiloxane elastomer and perfluoroether rubber and stretchable ionic conductive elastic fiber web are combined through mechanical interlocking technology to form an extremely environmentally stable fatigue-resistant self-adhesive ionic skin.
It achieves high mechanical properties, excellent environmental stability and adaptive surface adhesion in extreme environments, and improves the service life and application value of the material.
Smart Images

Figure CN119686133A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular relates to a fatigue-fracture-resistant self-adhesive ionic skin that is stable in extreme environments, and a preparation method and application thereof. Background Art
[0002] With the rapid development of the Internet of Things and artificial intelligence (AI), flexible wearable electronic devices that mimic human skin in responding to various environmental stimuli have attracted increasing attention. Inspired by natural biological systems, iontronics, as an emerging interdisciplinary technology based on precise ion control, has greatly enriched the selection of next-generation flexible electrode materials, shifting from traditional electronic conductors that require complex manufacturing processes or high costs to easily processed biomimetic ion conductors. Stretchable ion conductors, also known as ion skins, can be attached to the surface of human skin or soft robots as conformal sensors due to their softness and stretchability to quantify and monitor movement and electrophysiological activities in real time. Among them, hydrogels are considered to be ideal ion conductors due to their inherent biocompatibility and ionic conductivity. However, the problem of hydrogels being prone to freezing or evaporation under extreme temperature conditions severely limits their effectiveness in long-term sensing applications. Therefore, additional sealing measures or the use of anti-dehydration chemicals are usually required to solve the problem of moisture adsorption / desorption.
[0003] Ionic liquid gels are composed of a polymer network and its adsorbed ionic liquid. This type of gel is regarded as a potential alternative to hydrogels due to its unique non-volatility, wide operating temperature range and high ionic conductivity. However, these gels have problems with ionic liquid loss and biocompatibility (Adv. Funct. Mater. 2023, 35, 2314408). As an emerging alternative to ionic liquids, deep eutectic solvents (DES) are formed by hydrogen bonding interactions and have physicochemical properties similar to ionic liquids, such as high conductivity and low vapor pressure (Adv. Mater. 2023, 36, 2309576). However, DES-based low eutectic gels are still inherently sensitive to humidity / temperature and cannot compare with ionic liquid gels in terms of environmental tolerance. In addition, the above-mentioned stretchable ionic conductors are susceptible to contamination and damage by certain organic solvents. Overall, all types of stretchable ionic conductors currently have not yet adapted to the extremely harsh environments that soft robots may encounter, including underwater, extreme high and low temperatures, vacuum, and corrosive environments.
[0004] In addition, although previous studies have made important progress in the basic mechanical properties of stretchable ion conductors, such as stretchability and flexibility, the soft chain network formed by solvent swelling or salt plasticization and its relatively uniform structural design have resulted in these ion conductors being mostly poor in mechanical strength and robustness. In particular, this defect limits their ability to effectively resist damage and seriously affects their service life (PNAS2024,16,e2322684121). In view of the defects that may occur during use and the reversible deformation that requires the material to have good durability, these ion conductors are also required to have excellent fatigue fracture resistance. The current existing technologies for ion conductors are as follows:
[0005] CN116246815A discloses an ion conductor with high transparency and conductivity and its preparation method and application. The method directly mixes a crosslinking agent, an initiator, a monomer and an ionic liquid evenly and obtains the ion conductor through a polymerization reaction.
[0006] CN116239852A discloses an ion conductor and its preparation method and application. The preparation method of the ion conductor precursor solution comprises the following steps: mixing polyvinyl alcohol, phytic acid and water; wherein the mass ratio of polyvinyl alcohol to phytic acid is less than 0.4. The preparation method of the ion conductor comprises the following steps: drying the ion conductor precursor solution at 20-120°C.
[0007] It can be seen from the above patented technology that although the existing ion conductors have good ion conductivity, excellent biocompatibility, high sensitivity, good energy storage performance and piezoresistive response capabilities, the preparation process is complex and the cost is high. The most important thing is that the tolerance performance in extreme environments is still a defect, which obviously limits the application of ion conductors. Therefore, how to improve the mechanical properties (such as strain hardening, tear resistance and fatigue fracture resistance), environmental stability (high and low temperature resistance, waterproof and vacuum resistance) and adaptive surface adhesion of ion conductors based on their existing advantages, and use them in extreme environments, has become a difficult problem that technicians in the field of functional materials need to solve urgently. Summary of the invention
[0008] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a fatigue-fracture-resistant self-adhesive ionic skin that is stable in extreme environments and has simple process, excellent mechanical properties, extreme environment tolerance and adaptive surface adhesion ability, and a preparation method and application thereof.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments, characterized in that: the ionic skin is formed by combining chemically inert low-crosslinked polydimethylsiloxane elastomer and perfluoroether rubber with a stretchable ionic conductive elastic fiber mesh through a mechanical interlocking technology; wherein the polydimethylsiloxane elastomer is prepared by polymerization and curing of a silicone elastomer matrix and a PDMS curing agent, the perfluoroether rubber is obtained by volatilizing a perfluoroether rubber solution solvent, and the stretchable ionic conductive elastic fiber mesh is obtained by electrostatic spinning, and the strength of the ionic skin is ≥9.9MPa and the toughness is ≥10MJm -3 , tensile strain ≥355%, tensile toughness ≥5.7MJm -3 , fracture energy ≥71.6kJm -2 .
[0010] The above-mentioned extreme environment stable fatigue fracture resistant self-adhesive ionic skin, the mass ratio of the silicone elastomer matrix to the PDMS curing agent is 45:1-50:1; the loading concentration of the perfluoroether rubber solution is 0.8-1.2mLcm -2 The solvent evaporation conditions were set at 25°C for 10 minutes; the stretchable ion conductive elastic fiber mesh was prepared by electrospinning a spinning solution composed of a mixture of polyurethane particles, N,N-dimethylformamide, tetrahydrofuran and 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid.
[0011] A method for preparing a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments comprises the following steps:
[0012] 1. Preparation of ion conductive elastic fiber mesh:
[0013] (1) dissolving polyurethane particles in a mixture solution consisting of N,N-dimethylformamide and tetrahydrofuran, stirring at room temperature to obtain a uniform transparent polyurethane solution for later use;
[0014] (2) adding 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid to the polyurethane solution and stirring evenly to obtain a spinning solution;
[0015] (3) Using electrospinning technology, spinning is performed under certain conditions to obtain a stretchable ion conductive elastic fiber network;
[0016] 2. Curing interlocking treatment:
[0017] (4) uniformly mixing the silicone elastomer matrix and the PDMS curing agent to obtain a PDMS prepolymer for later use;
[0018] (5) scraping PDMS prepolymer on oil paper, covering any side of the ion conductive elastic fiber mesh on the oil paper scraped with PDMS prepolymer, and pre-curing, so that the PDMS prepolymer penetrates into the pores on one side of the ion conductive elastic fiber mesh by capillary action;
[0019] (6) placing the side that has been infiltrated with the prepolymer on oil paper coated with a certain thickness of PDMS prepolymer to form an adhesion layer on the surface that has been infiltrated with the PDMS prepolymer;
[0020] 3. Double-layer mechanical interlocking treatment:
[0021] (7) preparing a perfluoroether rubber solution of a certain concentration and injecting it into one side of the ion conductive elastic fiber mesh not filled with PDMS prepolymer to evaporate the solvent;
[0022] (8) The entire device is thermally cured in an oven to obtain a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments.
[0023] The method for preparing the above-mentioned extreme environment stable fatigue-resistant self-adhesive ionic skin, in the steps (1) and (2), the mass ratio of N,N-dimethylformamide to tetrahydrofuran is 1:1, the mass ratio of 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid to polyurethane particles is 1:1-1:4, and the mass percentage concentration of polyurethane in the spinning solution is 12-18wt%.
[0024] In the above-mentioned method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin, in the step (3), the working voltage of the spinning equipment is 12-18 kV, and the spinning rate is 0.1-0.4 mL h -1 , the drum speed is 200-600rpm.
[0025] In the above-mentioned method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin, in the step (4), the mass ratio of the silicone elastomer matrix to the PDMS curing agent is 45:1-50:1.
[0026] The above-mentioned method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin stable in extreme environments, in the step (5), the thickness of the PDMS prepolymer coated is 30-50 μm, the pre-curing temperature of the PDMS prepolymer is 80° C., and the pre-curing time is 130 s.
[0027] In the above-mentioned method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin, in the step (6), the thickness of the adhesive layer is 8-12 μm.
[0028] The above-mentioned method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin stable in extreme environments, in the step (7), the loading amount of the perfluoroether rubber is 0.8-1.2mLcm -2 The injection thickness of the perfluoroether rubber was 4.5 μm, and the solvent volatilization conditions were set at 25° C. for 10 minutes.
[0029] Application of ionic skin in the preparation of flexible and stretchable electronic devices for use in extreme environments.
[0030] The advantages of the preparation method and application of the fatigue-fracture-resistant self-adhesive ion skin of the present invention, which is stable in extreme environments, are as follows: a double-layer interlocking strategy is adopted, a low-crosslinked PDMS precursor is used as the main matrix and adhesion layer to penetrate into one side of the porous ion conductive elastic fiber network, and perfluoroether rubber is coated on the other side as an encapsulation layer, and the final ultra-thin composite ion skin material is obtained after thermal curing. The preparation process of the present invention is simple and efficient, with low cost, and the prepared composite ion skin has the advantages of good mechanical properties (such as strain hardening, tear resistance and fatigue fracture resistance), excellent environmental stability (high and low temperature resistance, waterproof and vacuum resistance) and adhesion of the adaptive surface, etc., excellent mechanical properties, and can withstand extreme environmental conditions. And the preparation process is simple and efficient, the preparation cost is low, and it is expected to be used in the fields of strain monitoring, temperature perception and self-powered sensing, and has a relatively wide range of application value and development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the structure of the fatigue-fracture-resistant self-adhesive ionic skin of the present invention that is stable in extreme environments;
[0032] Figure 2 This is a SEM image of the ionic skin prepared in Example 2;
[0033] Figure 3 This is a scanning electron microscope photograph of the ion conductive elastic fiber mesh obtained by electrospinning in Example 2;
[0034] Figure 4 SEM images of the pore structure of the surface layer of PDMS and ion conductive elastic fiber mesh: (a) side view; (b) top view;
[0035] Figure 5 The stress-strain curves of the ionic skin prepared in Example 2 under two different conditions, with or without a notch;
[0036] Figure 6 This is a relationship diagram between the crack extension dc / dN per cycle of the ion skin prepared in Example 2 and the energy release rate of the composite ion skin;
[0037] Figure 7 This is a test diagram of the adhesion of the ionic skin prepared in Example 2 to various substrates in air and underwater;
[0038] Figure 8 This is a scanning electron microscope photograph of the ionic skin prepared in Example 2 adhered to pig skin, showing a seamless adhesion interface between the composite ionic skin and pig skin;
[0039] Fig. 9 This is a graph showing the change in ionic skin environmental tolerance data obtained in Example 2. Except for the high temperature test, other environmental temperatures were controlled at 25°C, and the measured mass and ionic conductivity of the material were maintained under each condition for 12 hours. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] In the present invention, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the attached drawings; while "inside" and "outside" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order. The term "plurality" means "two or more".
[0042] like Figure 1-4 As shown, a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments is formed by combining chemically inert low-crosslinked polydimethylsiloxane elastomer and perfluoroether rubber with a stretchable ionic conductive elastic fiber mesh through a mechanical interlocking technology; wherein the polydimethylsiloxane elastomer is prepared by polymerization and curing of a silicone elastomer matrix and a PDMS curing agent, the perfluoroether rubber is obtained by evaporating the solvent of a perfluoroether rubber solution, and the stretchable ionic conductive elastic fiber mesh is obtained by electrostatic spinning, and the strength of the ionic skin is ≥9.9MPa and the toughness is ≥10MJm -3 , tensile strain ≥355%, tensile toughness ≥5.7MJm -3 , fracture energy ≥71.6kJm -2 .
[0043] A method for preparing a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments comprises the following steps:
[0044] 1. Preparation of ion conductive elastic fiber mesh:
[0045] (1) dissolving polyurethane particles in a mixture solution consisting of N,N-dimethylformamide and tetrahydrofuran, stirring at room temperature to obtain a uniform transparent polyurethane solution for later use;
[0046] (2) adding 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid to the polyurethane solution and stirring evenly to obtain a spinning solution;
[0047] (3) Using electrospinning technology, spinning is performed under certain conditions to obtain a stretchable ion conductive elastic fiber network;
[0048] 2. Curing interlocking treatment:
[0049] (4) uniformly mixing the silicone elastomer matrix and the PDMS curing agent to obtain a PDMS prepolymer for later use;
[0050] (5) scraping PDMS prepolymer on oil paper, covering any side of the ion conductive elastic fiber mesh on the oil paper scraped with PDMS prepolymer, and pre-curing, so that the PDMS prepolymer penetrates into the pores on one side of the ion conductive elastic fiber mesh by capillary action;
[0051] (6) placing the side that has been infiltrated with the prepolymer on oil paper coated with a certain thickness of PDMS prepolymer to form an adhesion layer on the surface that has been infiltrated with the PDMS prepolymer;
[0052] 3. Double-layer mechanical interlocking treatment:
[0053] (7) preparing a perfluoroether rubber solution of a certain concentration and injecting it into one side of the ion conductive elastic fiber mesh not filled with PDMS prepolymer to evaporate the solvent;
[0054] (8) The entire device is thermally cured in an oven to obtain a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments.
[0055] The ionic skin of the present invention can be used to prepare flexible and stretchable electronic devices under extreme environmental requirements, and has a wide range of application value and development prospects in the fields of strain monitoring, temperature sensing and self-powered sensing.
[0056] Among them, polyurethane was purchased from Taiwan Risheng Company, China, with the item number BTE-75A; N,N-dimethylformamide was purchased from Sigma, with the item number 227056; tetrahydrofuran was purchased from Sigma, with the item number 401757; polydimethylsiloxane elastomer (PDMS prepolymer) was purchased from Dow Corning, USA, with the item number 184, composed of PDMS silicone elastomer matrix and PDMS curing agent; perfluoroether rubber was purchased from Shanghai Institute of Organic Chemistry, with the item number of low temperature resistant type; 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide salt was purchased from Aladdin Company, with the item number of 174899-82-2; Performance Fluid was purchased from 3M Company, USA, PF-5060.
[0057] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0058] Embodiment 1:
[0059] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0060] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N, N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:1 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 12wt%.
[0061] 2. The spinning solution was spun at a voltage of 12 kV at a spinning rate of 0.1 mL / h -1 , wrap aluminum foil on the drum, set the drum speed to 200 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh, such as Figure 3 shown.
[0062] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 45:1 to prepare PDMS prepolymer, and use a scraper to scrape a 30 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0063] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0064] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 8 μm thick PDMS prepolymer to form an adhesion layer.
[0065] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid into the side without PDMS filling, that is, into the sticky PET frame, with a volume loading of 0.8 mL cm-2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0066] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 , 2 shown.
[0067] Embodiment 2:
[0068] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0069] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N,N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:2 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 14wt%.
[0070] 2. The spinning solution was spun at a voltage of 15.8 kV and a spinning rate of 0.2 mL h -1 , wrap aluminum foil on the drum, set the drum speed to 300 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh with a fiber diameter of about 1.27 μm, such as Figure 3 shown.
[0071] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 50:1 to prepare PDMS prepolymer, and use a scraper to scrape a 40 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0072] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0073] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 10 μm thick PDMS prepolymer to form an adhesion layer.
[0074] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid as the solvent into the sticky PET frame without PDMS filling, with a volume loading of 1 mL cm -2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0075] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 , 2 shown.
[0076] Embodiment 3:
[0077] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0078] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N, N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:4 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 14wt%.
[0079] 2. The spinning solution was spun at a voltage of 13.9 kV and a spinning rate of 0.2 mL / h -1 , wrap aluminum foil on the drum, set the drum speed to 300 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh, such as Figure 3 shown.
[0080] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 46:1 to prepare PDMS prepolymer, and use a scraper to scrape a 35 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0081] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0082] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 9 μm thick PDMS prepolymer to form an adhesion layer.
[0083] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid solvent into the side without PDMS, that is, into the sticky PET frame, with a volume loading of 0.9 mL cm -2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0084] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 , 2 shown.
[0085] Embodiment 4:
[0086] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0087] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N, N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:3 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 14wt%.
[0088] 2. The spinning solution was spun at a voltage of 16.7 kV and a spinning rate of 0.3 mL / h -1 , wrap aluminum foil on the drum, set the drum speed to 400 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh, such as Figure 3 shown.
[0089] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 47:1 to prepare PDMS prepolymer, and use a scraper to scrape a 40 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0090] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0091] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 10 μm thick PDMS prepolymer to form an adhesion layer.
[0092] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid as the solvent into the sticky PET frame without PDMS filling, with a volume loading of 1 mL cm -2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0093] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 , 2 shown.
[0094] Embodiment 5:
[0095] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0096] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N, N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:2 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 15wt%.
[0097] 2. The spinning solution was spun at a voltage of 17.5 kV and a spinning rate of 0.4 mL / h -1 , wrap aluminum foil on the drum, set the drum speed to 500 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh, such as Figure 3 shown.
[0098] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 48:1 to prepare PDMS prepolymer, and use a scraper to scrape a 45 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0099] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0100] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 11 μm thick PDMS prepolymer to form an adhesion layer.
[0101] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid into the side not filled with PDMS, that is, into the sticky PET frame, with a volume loading of 1.1 mL cm -2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0102] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 , 2 shown.
[0103] Embodiment 6:
[0104] The method for preparing the fatigue-resistant and fracture-resistant self-adhesive ionic skin of this embodiment comprises the following steps:
[0105] 1. A certain amount of polyurethane particles were dissolved in a mixture solution consisting of N, N-dimethylformamide and tetrahydrofuran (1 / 1, wt / wt), and stirred at room temperature for 24 hours to obtain a uniform transparent polyurethane solution. 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid was added to the polyurethane solution in a mass ratio of 1:2 to polyurethane particles, and stirred for 2 hours to obtain a spinning solution with a polyurethane concentration of 18wt%.
[0106] 2. The spinning solution was spun at a voltage of 18 kV at a spinning rate of 0.2 mL / h -1 , wrap aluminum foil on the drum, set the drum speed to 600 rpm, and the working distance from the needle to the collector to 11 cm to obtain an ion conductive elastic fiber mesh, such as Figure 3 shown.
[0107] 3. Evenly mix the silicone elastomer matrix and PDMS curing agent at a mass ratio of 49:1 to prepare PDMS prepolymer, and use a scraper to scrape a 50 μm thick PDMS prepolymer solution on oil paper on an AFA-Ⅱ automatic coating machine. Cover the sticky PET frame on either side of the ion conductive elastic fiber mesh for subsequent operations.
[0108] 4. Cover the other side of the ion conductive elastic fiber mesh directly on the oil paper coated with PDMS prepolymer and pre-cure it at 80°C for 130s. The PDMS prepolymer will quickly penetrate into the pores of the ion conductive elastic fiber mesh through capillary action, and leave micropores on the upper surface to form an interlocking structure with the encapsulation layer, such as Figure 4 By controlling the pre-curing time of PDMS, it can completely penetrate into the fiber network except the upper surface.
[0109] 5. After pre-curing, place the side that has been infiltrated with PDMS prepolymer on oil paper coated with 12 μm thick PDMS prepolymer to form an adhesion layer.
[0110] 6. Dissolve 0.1 g of perfluoroether rubber in 20 g of 3M PF-5060 solvent as the encapsulation solution. Then, inject the perfluoroether rubber solution with Performance Fluid into the side without PDMS filling, that is, into the sticky PET frame, with a volume loading of 1.2 mL cm -2 The perfluoroether rubber has a thickness of 4.5 μm and forms a mechanical interlocking structure with the fiber network. It is then slowly dried at room temperature.
[0111] 7. The whole device was cured in an oven at 80°C for 2 hours to obtain the final double-layer mechanical interlocking composite ion skin, i.e., the extreme environment stable fatigue fracture resistant self-adhesive ion skin of the present invention, such as Figure 1 ,2 shown.
[0112] The performance test results of the extreme environment stable fatigue fracture resistant self-adhesive ionic skin prepared in Example 2 of the present invention are as follows:
[0113] like Figure 1-4 As shown, two interlocking layers are formed on both sides of the ion conductive elastic fiber mesh 1, namely: an interlocking layer 3 formed by a polydimethylsiloxane elastomer 2 and an interlocking layer 5 formed by a perfluoroether rubber layer 4, and a plurality of hanging chains 6 are provided in the interlocking layer 3. The ion conductive elastic fiber mesh 1 contains a hard segment 1-1 and a soft segment 1-2, and the ionic liquid 8 has a plurality of positive and negative charges, which attach the hard segment 1-1 to the soft segment 1-2, making the structure more stable. From the SEM image of the cross section of the material, it can be seen that the embedded ion fiber network is evenly distributed in the PDMS and perfluoroether rubber 7. This interlocking structure is not only conducive to structural stability, but also conducive to the transmission of stress during deformation. The rearrangement of the randomly oriented fiber network in the matrix gives the ion skin mechanical properties similar to those of human skin. The mechanical properties of the material were characterized using a universal testing machine. The composite ion skin presents a specific "J-shaped" stress-strain curve, which is very similar to the strain hardening characteristics of human skin: a large deformation occurs at low stress, and its modulus gradually increases with the increase of strain, and finally the stress increases almost linearly before failure. In summary, from the perspective of mechanical biomimetic, the low initial modulus of ionic skin (0.9 MPa) is close to that of human skin (0.42-3.7 MPa), and the strain (250%) without obvious hardening during stretching is much higher than the natural deformation of human skin (<80%), all of which ensure good matching with the skin. At the same time, the high strength (9.9 MPa) and high toughness (10 MJ m -3 ) can protect against tensile damage.
[0114] like Figure 5 As shown in Figure 2, for the notched ion skin, the final stress-strain curve still shows the effect of strain hardening. The tensile strain, tensile toughness and fracture energy of the notched composite ion skin are as high as ~355%, 5.7 MJm -3 and 71.6 kJ m -2 Next, the fatigue fracture resistance of the samples was characterized by cyclic loading-unloading tests. The composite ion skin can withstand 50,000 cycles at 300% strain, which clearly shows the important role of the ion fiber mesh in improving the fatigue fracture resistance of the material. In addition, by recording the crack propagation during stretching, it was calculated that the fatigue threshold of the composite ion skin reached the highest value of stretchable materials, ~12.4 kJ m -2 .
[0115] like Figure 6As shown in Figure 2, adhesion is crucial for sensors applied to curved skin that is constantly deforming, as they always produce high-quality signals due to conformal contact with the skin. PDMS with a low degree of cross-linking not only enables the composite ionic skin to have good adhesion to various material surfaces, but also effectively avoids the leakage problem of ionic liquids, making the ionic skin have good biocompatibility. According to the SEM of the adhesion of the composite ionic skin to pig skin, a mechanical interlocking structure with no gap residue can be seen at the formed interface, indicating that the composite ionic skin has good interface-adaptive adhesion ability. In addition, as Figure 7 As shown in Figure 1, the 90° peel test was used to quantitatively measure the adhesion strength of the material to various substrates. Figure 7-9 As shown, except for pigskin and wood with strong water absorption, the adhesion strength of the composite ionic skin to these substrates was almost unaffected by moisture, indicating that it can be directly and stably applied to the surfaces of these materials without the aid of other adhesive tapes.
[0116] To further evaluate the environmental stability of the material, the changes in properties were studied after the composite ion skin was treated with different humidity, salt solutions, vacuum and high temperature. Since the ion fiber network is tightly embedded in the inherently inert PDMS and perfluoroether rubber, and the ionic liquid in the ion fiber is difficult to volatilize, the weight, ionic conductivity and mechanical properties of the composite ion skin are stable under various environmental conditions, and it is resistant to high and low temperatures, waterproof and vacuum, showing the potential for long-term application.
[0117] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.
Claims
1. A self-adhesive ionic skin that is stable in extreme environments and resistant to fatigue fracture, characterized by: The ionic skin is formed by combining chemically inert low-crosslinked polydimethylsiloxane elastomer and perfluoroether rubber with a stretchable ion conductive elastic fiber mesh through a mechanical interlocking technology; wherein the polydimethylsiloxane elastomer is prepared by polymerization and curing of a silicone elastomer matrix and a PDMS curing agent, the perfluoroether rubber is obtained by evaporating a perfluoroether rubber solution solvent, and the stretchable ion conductive elastic fiber mesh is obtained by electrostatic spinning. The strength of the ionic skin is ≥9.9MPa and the toughness is ≥10MJm -3 , tensile strain ≥355%, tensile toughness ≥5.7MJm -3 , fracture energy ≥71.6kJm -2 .
2. The extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 1 is characterized by: The mass ratio of the silicone elastomer matrix to the PDMS curing agent is 45:1-50:1; the loading amount of the perfluoroether rubber solution is 0.8-1.2 mL cm -2 The solvent evaporation conditions were set at 25°C for 10 minutes; the stretchable ion conductive elastic fiber mesh was prepared by electrospinning a spinning solution composed of a mixture of polyurethane particles, N,N-dimethylformamide, tetrahydrofuran and 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid.
3. A method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claims 1-2, characterized in that: The steps include:
1. Preparation of ion conductive elastic fiber mesh: (1) dissolving polyurethane particles in a mixture solution consisting of N,N-dimethylformamide and tetrahydrofuran, stirring at room temperature to obtain a uniform transparent polyurethane solution for later use; (2) adding 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid to the polyurethane solution and stirring evenly to obtain a spinning solution; (3) Using electrospinning technology, spinning is performed under certain conditions to obtain a stretchable ion conductive elastic fiber network; 2. Curing interlocking treatment: (4) uniformly mixing the silicone elastomer matrix and the PDMS curing agent to obtain a PDMS prepolymer for later use; (5) scraping PDMS prepolymer on oil paper, covering any side of the ion conductive elastic fiber mesh on the oil paper scraped with PDMS prepolymer, and pre-curing, so that the PDMS prepolymer penetrates into the pores on one side of the ion conductive elastic fiber mesh by capillary action; (6) placing the side that has been infiltrated with the prepolymer on oil paper coated with a certain thickness of PDMS prepolymer to form an adhesion layer on the surface that has been infiltrated with the PDMS prepolymer; 3. Double-layer mechanical interlocking treatment: (7) preparing a perfluoroether rubber solution of a certain concentration and injecting it into one side of the ion conductive elastic fiber mesh not filled with PDMS prepolymer to evaporate the solvent; (8) The entire device is thermally cured in an oven to obtain a fatigue-resistant and fracture-resistant self-adhesive ionic skin that is stable in extreme environments.
4. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3 is characterized by: In the steps (1) and (2), the mass ratio of N,N-dimethylformamide to tetrahydrofuran is 1:1, the mass ratio of 1-ethyl-3-methylimidazole-bis(trifluoromethylsulfonyl)imide salt ionic liquid to polyurethane particles is 1:1-1:4, and the mass percentage concentration of polyurethane in the spinning solution is 12-18wt%.
5. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3, characterized in that: In step (3), the working voltage of the spinning equipment is 12-18 kV, and the spinning rate is 0.1-0.4 mL h -1 , the drum speed is 200-600rpm.
6. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3, characterized in that: In the step (4), the mass ratio of the silicone elastomer matrix to the PDMS curing agent is 45:1-50:
1.
7. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3, characterized in that: In the step (5), the thickness of the PDMS prepolymer applied by scraping is 30-50 μm, the pre-curing temperature of the PDMS pre-polymer is 80° C., and the pre-curing time is 130 s.
8. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3, characterized in that: In the step (6), the thickness of the adhesion layer is 8-12 μm.
9. The method for preparing the extreme environment stable fatigue fracture resistant self-adhesive ionic skin according to claim 3, characterized in that: In the step (7), the loading amount of the perfluoroether rubber is 0.8-1.2 mL cm -2 The injection thickness of the perfluoroether rubber was 4.5 μm, and the solvent volatilization conditions were set at 25° C. for 10 minutes.
10. Use of the ionic skin as claimed in claims 1-2 in preparing flexible and stretchable electronic devices for use in extreme environments.
Citation Information
Patent Citations
Low-temperature-resistant perfluoroether rubber composition as well as preparation method and application thereof
CN112457612A
High-mechanical-strength self-repairing self-adhesive polysiloxane elastomer and preparation method thereof
CN114672027A
Conductive self-adhesive nanofiber membrane as well as preparation method and application thereof
CN116289226A
Flexible multifunctional sensor, system and preparation method
CN116295634A